2020
DOI: 10.1001/jamaoncol.2019.4117
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility and Radiologic Assessment for Adjuvant Clinical Trials in Kidney Cancer

Abstract: To harmonize the eligibility criteria and radiologic disease assessment definitions in clinical trials of adjuvant therapy for renal cell carcinoma (RCC).METHOD On November 28, 2017, US-based experts in RCC clinical trials, including medical oncologists, urologic oncologists, regulators, biostatisticians, radiologists, and patient advocates, convened at a public workshop to discuss eligibility for trial entry and radiologic criteria for assessing disease recurrence in adjuvant trials in RCC. Multiple virtual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…A recent study from Raddia et al supported our findings, and they suggested that the thorough clinical staging with preoperative imaging studies was an important factor for identifying the high-risk LN+ group and providing the beneficiary role of LND in the survival outcomes of nmRCC patients who underwent curative nephrectomy 20,21 . In these backgrounds, a recent adjuvant clinical trial suggesting several eligibility and radiologic assessments for kidney cancer that either CT or MRI within 4 weeks should be performed, and every patient with microscopically positive soft tissue or vascular margins without gross residual or radiologic disease may be included in trials to all suspicious regional lymph nodes 22 . Thus, previous papers supported the complete removal of suspicious LN, and the efficacy of LN dissection is important for survival prognoses [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from Raddia et al supported our findings, and they suggested that the thorough clinical staging with preoperative imaging studies was an important factor for identifying the high-risk LN+ group and providing the beneficiary role of LND in the survival outcomes of nmRCC patients who underwent curative nephrectomy 20,21 . In these backgrounds, a recent adjuvant clinical trial suggesting several eligibility and radiologic assessments for kidney cancer that either CT or MRI within 4 weeks should be performed, and every patient with microscopically positive soft tissue or vascular margins without gross residual or radiologic disease may be included in trials to all suspicious regional lymph nodes 22 . Thus, previous papers supported the complete removal of suspicious LN, and the efficacy of LN dissection is important for survival prognoses [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…In these backgrounds, a recent adjuvant clinical trial suggesting several eligibility and radiologic assessments for kidney cancer that either CT or MRI within 4 weeks should be performed, and every patient with microscopically positive soft tissue or vascular margins without gross residual or radiologic disease may be included in trials to all suspicious regional lymph nodes 22 . Thus, previous papers supported the complete removal of suspicious LN, and the efficacy of LN dissection is important for survival prognoses [22][23][24] . Babaian et al 23 showed the effectiveness of LN dissection in 1270 nmRCC patients and reported that OS, CSS, and RFS among pNx, pN0, and pN1 cases were statistically significant (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Low-grade RCC patients may undergo partial nephrectomy, whereas high-grade RCC patients may require more invasive and extensive surgery. 34 As an important prognostic factor, it is important to preoperatively differentiate the grade of RCC in clinical practice and provide more valuable guidance for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in renal function may affect trial results; for example, patients with chronic renal dysfunction may have shorter survival. 35 Thus, trials requiring better renal function may generate better results. In total, 3/4 trials requiring a higher creatinine clearance were newer immunotherapy trials, possibly because of concern that immunotherapies may cause immune-mediated renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Some also suggest loosening or omiting renal function criteria altogether from RCC trials if study agents are not renally metabolized, thus expanding access to clinical trials for RCC patients. 35 The 29 mRCC trials also differed in whether or not they considered patients with CNS metastases as trial eligible. Over one third of the trials disallowed CNS metastases (Fig.…”
Section: Discussionmentioning
confidence: 99%